Physical Self-Image: Classical, Non-Classical, and Post-Non-Classical Aspects - O. I. Chernyshova (СибСкрипт)
This theoretical study reviews the phenomena of physical self-image across psychological approaches, i. e., natural-scientific, cultural, activity-based, psychoanalytic, humanistic, cognitive, and constructional. The methodological aim was to identify the similarities and differences in the way the phenomena of physicality are described in various psychological approaches, as well as from the perspectives of rationality. Individual interpretations were analyzed in line with the classical, non-classical, and post-non-classical paradigms introduced by V. S. Stepin. The classification relied on the ideas about paradigmatic shifts expressed by V. A. Lektorskiy, A. G. Asmolov, and D. A. Leontiev. The physical self-images that correspond to the classical ideal of rationality follow the idea of body scheme and represent the mechanistic or physiological views on physicality. The non-classical views introduce the concept of physical self-image as a product of self-consciousness, specific in relation to the concept of self-image. In the post-non-classical ideal of rationality, the physical self-image is a cognitive construct that describes one’s ideas about one’s physicality at the levels of the organism, society, and culture. The classification of similarities and differences of the physical self-image across paradigms revealed the major directions in physicality studies with practical application prospects.